The Effectiveness of Peer Education Methods in Increasing Tuberculosis Knowledge in High School Students - Ferdi Riansyah; Nadia Sari; Seri Warzukni; Elvina Sari; Niswatul Khaira; Nuril Ria Alifa; Mhd. Hidayattullah; Nisrina Hanum; Reka Julia Utama; Muliana Muliana; Gadis Halizasia; Said Usman; Ristiani Ristiani; Abdul Ajiz (Jurnal Ragam Pengabdian, 2026)
This study aimed to determine the effectiveness of the peer education method in improving tuberculosis knowledge among high school students. The problem addressed in this research was the limited understanding of tuberculosis among adolescents, which may influence prevention behavior and awareness. The study used a quantitative approach with a quasi-experimental one group pretest–posttest design. The research was conducted in February 2025 at a senior high school, involving 112 students selected using a total sampling technique. Data were collected using a structured questionnaire that measured students’ knowledge before and after the educational intervention. The intervention was delivered through peer education, where trained students provided health education sessions, group discussions, and interactive learning activities to their classmates. Data analysis was conducted using descriptive analysis to describe respondent characteristics and comparative analysis to examine changes in knowledge levels before and after the intervention. The results showed that students’ knowledge improved after receiving peer education, indicating that this method helped students better understand information related to tuberculosis. The study concludes that peer education is an effective approach for increasing adolescents’ health knowledge because it encourages active participation, comfortable communication, and better information acceptance among students.